A fretting wear model considering formation of tribolayers - Yulei Yang; Jimin Xu; Yi Liang (Industrial Lubrication and Tribology, 2023)
Purpose Quantitative fretting wear prediction is of practical significance for industrial components. This study aims to establish a fretting wear model considering the formation of tribolayers and provide better fretting wear prediction. Design/methodology/approach Based on the characteristics for the formation of tribolayers, the ratio of fretting amplitude to nominal contact area length in the fretting direction is used to characterize their formation and contribution to the wear volume. The wear volume is then associated with the product of the friction energy and the ratio of fretting amplitude to nominal contact area length. Findings Better prediction in the wear volume can be achieved with the proposed fretting wear model by taking the formation of tribolayers into consideration. Originality/value The contribution of the formation of tribolayers to the wear volume is considered in the model and better prediction can be achieved. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-01-2023-0004/